Storm on Snowbelle Mountain - Elliott, Rebecca (2022)
Despite disagreements on the wisdom of the adventure, Rainbow Tinseltail and the other unicorns set out for Snowbelle Mountain to find out if Yetis are real--and when they get caught in a blizzard and take shelter in a cave they find the answer to their quest.
Keywords: Unicorns -- Juvenile fiction; Yeti -- Juvenile fiction; Blizzards -- Juvenile fiction; Friendship -- Juvenile fiction; Unicorns -- Fiction; Yeti -- Fiction; Blizzards -- Fiction; Friendship -- Fiction; Diaries -- Fiction